THE ROLE OF WALI, ANCIENT MOSQUES AND SACRED TOMBS IN THE DYNAMICS OF ISLAMISATION IN LOMBOK - Budiwanti, Erni (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2014)
This paper highlights specifically the inter-relationship amidst the Wali, ancient mosques and sacred tombs (makam) playing vital role in the process of Islamization in the Indonesian archipelago, and in Lombok in particular. The process of converting local religion to Islam involves Wali - a venerated religious figure coming from outside Lombok- and the tangible legacies that he left in the forms of keramat creating new tradition of ziarah. The early stage of conversion was strongly marked by contextualizing Islam into local cultural symbol and cosmology. Embedded in this stage is the development of venerated attributes attached to keWalian, in the forms of: karamah, ngalap berkah, and wasilah. These spiritual attributes are pinpointed to highlight a dis¬tinctive cultural variance of Sasak Muslims in Lombok.